2020
DOI: 10.1158/1078-0432.ccr-20-0269
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Activation by Metformin Promotes Survival of Dormant ER+ Breast Cancer Cells

Abstract: Purpose: Despite adjuvant endocrine therapy for patients with estrogen receptor alpha (ER)-positive breast cancer, dormant residual disease can persist for years and eventually cause tumor recurrence. We sought to deduce mechanisms underlying the persistence of dormant cancer cells to identify therapeutic strategies. Experimental Design: Mimicking the aromatase inhibitor-induced depletion of estrogen levels used to treat patients, we developed preclinical models of dormancy in ER+ breast cancer induced by estr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 50 publications
0
47
0
Order By: Relevance
“…According to previous studies, CPT1A amplification was found in 20% of ER-positive breast cancer cases, and the CPT1A protein level is elevated in most breast cancer cell lines [ 41 ]. CPT1A is regulated by c-MYC or AMPK in breast cancer, and promotes breast cancer metastasis or therapeutic resistance through several oncogenic signaling pathways, such as VEGF, ERK and Src pathways [ 25 – 27 , 29 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, CPT1A amplification was found in 20% of ER-positive breast cancer cases, and the CPT1A protein level is elevated in most breast cancer cell lines [ 41 ]. CPT1A is regulated by c-MYC or AMPK in breast cancer, and promotes breast cancer metastasis or therapeutic resistance through several oncogenic signaling pathways, such as VEGF, ERK and Src pathways [ 25 – 27 , 29 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Previous studies have shown that metformin can exert antineoplastic effects by recruiting the kinase enzyme activated by adenosine monophosphate (AMPK) and reducing the phosphorylation of protein kinase B, mammalian target of rapamycin (mTOR), and p70S6k in different types of tumors. [ 18,19 ] In addition, metformin regulates apoptosis signaling [ 20 ] by inhibiting phosphorylation of BAD and Bcl‐2, procaspase 9, procaspase 3, and procaspase 7, and upregulation of BAD, cytochrome c, and Apaf‐1 protein. [ 21,22 ] However, metformin is capable of affecting the mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…Controversially, metformin may have the negative effect of accelerating cancer development. The recent in vitro and in vivo results of the study by Hampsch et al suggested that metformin may promote the survival of dormant estrogen receptor (ER)-positive breast cancer cells by activating AMPK in a context-dependent manner [143]. Therefore, despite recent evidence supporting the anticancer and chemopreventive effects of metformin, the context-dependent effects of AMPK in cancer must be considered in the future when administering metformin as a chemoprevention or adjuvant treatment [144].…”
Section: Discussionmentioning
confidence: 99%